Acid-Base Balance (Out of Print) - Alan Grogono (Association of American Medical Colleges, 2006)
Abstract This educational website was created based on a lifetime of teaching and provides a comprehensive tutorial on human acid-base balance for all healthcare professions. It is written for students, residents, faculty, and practitioners.